Determinación de impactos socio ambientales generados por la acción antropogénica en el centro de producción Sacha-Wiwa parroquia de Guasaganda cantón La Maná periodo 2021-2022. - Jaramillo Moya, Andderson Enrique (2022)
This research aimed to determine the socio-environmental impact generated by anthropogenic action in the sector. To do so, we first identified all the production processes carried out through the review of information provided by the research center and the on-site visit where we could reference and observe the state in which the study area was. In order to identify the different impacts caused by human intervention, environmental sustainability indicators were established to quantify the degree of responsibility and environmental sustainability of the site. The economic and environmental impacts generated by the Higher Education Institutions and Research Institutes in the modification and introduction of germplasm which the deterioration of the study area has evidenced; soil erosion, degradation of natural resources, especially water quality, which affects the lower part of the basin significantly. The land covers 115 ha dedicated to agriculture and livestock production, mainly coffee, cocoa, sugar cane, and pasture; the latter is used to feed cattle and their respective research and commercialization projects. Finally, a decision framework was implemented for recovery models that allow the restoration and conservation of the site, which is necessary to balance social, environmental, and economic aspects.